A Risk Assessment of Underwater Cultural Heritage for Wave-Induced Hazards: The Impact of Climate Change on Cadiz Bay - C. Ferrero-Martín; A. Izquierdo; M. Bethencourt; T. Fernández-Montblanc (Journal of Marine Science and Engineering)
The combination of future changes in sea levels and wave climate in coastal areas represents one of the greatest threats to the preservation of underwater cultural heritage (UCH). This study presents a new methodology to assess climate change’s impacts on UCH preservation in shallow waters, focusing on wave-induced hazards like decontextualization, scouring, and wear erosion. The approach uses hybrid downscaling of bias-corrected wave fields from the RCP4.5 and RCP8.5 CMIP5 scenarios. The methodology was applied in the Bay of Cadiz, where an overall reduction in wave energy flux was observed. However, local increases were detected in rocky outcrops and coastal areas with high UCH density. As a result, the shallow zones exhibited significant changes in decontextualization and scouring hazards. However, the most relevant risk changes were linked to wear erosion, particularly at sites on rocky outcrops near Cadiz. The methodology proposed in this study is essential for identifying areas with higher risk and for evaluating UCH preservation under future climate conditions. It offers an effective tool for discriminating sites at risk and for conducting a long-term assessment of these risks in coastal environments affected by climate change.